Engaging culture and context in mhGAP implementation: fostering reflexive deliberation in practice - Laurence J Kirmayer; Ana Gómez-Carrillo; Raphael Lencucha; Neda Faregh; Samuel Veissière (BMJ Global Health)
In 2002, WHO launched the Mental Health Gap Action Programme (mhGAP) as a strategy to help member states scale up services to address the growing burden of mental, neurological and substance use disorders globally, especially in countries with limited resources. Since then, the mhGAP program has been widely implemented but also criticised for insufficient attention to cultural and social context and ethical issues. To address this issue and help overcome related barriers to scale-up, we outline a framework of questions exploring key cultural and ethical dimensions of mhGAP planning, adaptation, training, and implementation. This framework is meant to guide mhGAP activity taking place around the world. Our approach is informed by recent research on cultural formulation and adaptation, and aligned with key components of the WHO implementation research guide (Peters, D. H., Tran, N. T., & Adam, T. (2013). Implementation research in health: a practical guide. Implementation research in health: a practical guide.). The framework covers three broad domains: (1) Concepts of wellness and illness—how to examine cultural norms, knowledge, values and attitudes in relation to the “culture of the mhGAP”; (2) Systems of care—identifying formal and informal systems of care in the cultural context of practice.; and (3) Ethical space: examining issues related to power dynamics, communication, and decision-making. Systematic consideration of these issues can guide integration of cultural knowledge, structural competence, and ethics in implementation efforts.